Mexican cinema beyond borders: approximation to the activities of José U. Calderon - Flores, Silvana (2018)
The objective of this article is to make an approach to the work of the exhibitor and distributor José U. Calderón as an initial platform for the production of Mexican cinema business initiated later through his sons (Pedro, José Luis and Guillermo), along the decades. For that purpose, we will show the foundation of Azteca Films, Inc. (enterprise dedicated to the exhibition of Mexican cinema in United States) and of the movie theatres located in cities on both sides of US-Mexico borders, noticing their corresponding relevance for the regional and international development of Mexican cinema. We find that the work of Calderon in the Mexican cinema industry, taking into account his role as a diffuser of that industry outside the national territory, has been of great importance; and if we understand that there are very few historiographical references about his place as an entrepreneur, we consider it is necessary to make an historical approximation about his activities and the family enterprises he founded. The analysis will connect the concept of transnationalism to the advance of those industrial ventures, framing the Mexican cinema in its first decades of development around a search that exceeds the strictly national boundaries.